Analisis Kepuasan Pengguna Aplikasi Spotify menggunakan Metode End-User Computing Satisfaction (EUCS) - Rama, M Bryant Rama Ajalal; Muhammad Jazman; Tengku Khairil Ahsyar; Syaifullah (The Indonesian Journal of Computer Science, 2024)
The increasing use of digital applications among fan communities encourages the importance of understanding the factors that influence user satisfaction. This study aims to analyze the influence of Content, Accuracy, Format, Ease of Use, and Timeliness on user satisfaction in the Weverse application. Using a quantitative approach with multiple linear regression methods, this study examines the effect of independent variables on the dependent variable. The analysis results show that Accuracy, Format, and Ease of Use have a significant influence on user satisfaction, while Content and Timeliness have no significant effect. Simultaneously, all independent variables contribute 54.1% to user satisfaction, based on the Adjusted R Square results. In conclusion, technical factors such as information accuracy, ease of use, and presentation format play an important role in increasing app user satisfaction, while content and timeliness of information have a smaller role. The findings provide valuable insights for app developers in improving user experience and maintaining customer loyalty in the competitive digital age.